Evaluating the effects of two alcohol reduction counseling interventions on intimate partner violence perpetration: secondary analysis of a three‐arm randomized controlled trial among Vietnamese men with HIV. (27th April 2021) - Hershow, Rebecca B.; Reyes, H. Luz Mc Naughton; Ha, Tran Viet; Chander, Geetanjali; Mai, Nguyen Vu Tuyet; Sripaipan, Teerada; Dowdy, David W.; Latkin, Carl; Hutton, Heidi E.; Pettifor, Audrey; Maman, Suzanne; Frangakis, Constantine; et al.
Abstract: Background and Aims: Evidence suggests that alcohol reduction interventions decrease intimate partner violence (IPV) perpetration, although this remains untested in low‐ and middle‐income countries and among men with human immunodeficiency virus (HIV). This study evaluates the effectiveness of alcohol reduction counseling interventions on IPV perpetration among men on anti‐retroviral therapy (ART) and tests whether alcohol use explains the intervention effects. Design: Secondary analysis of data from a three‐arm randomized controlled trial among ART patients with hazardous alcohol use. Participants were recruited from March 2016 to May 2017. Setting: Thai Nguyen, Vietnam. Participants, interventions and comparators: Male participants ( n  = 426). Participants received a two‐session brief intervention (BI), a six‐session combined intervention (CoI) or the standard of care (SOC), comprising alcohol treatment referrals. Alcohol reduction counseling interventions were guided by cognitive–behavioral therapy and motivational enhancement therapy delivered by psychosocial counselors over 3 months. Measurements: IPV perpetration was measured using the shortened Conflict Tactics Scale 2 and alcohol use was measured using timeline followback. Findings: BI and CoI participants reported reduced IPV perpetration at 3 months compared with SOC participants [BI: adjusted odds ratio (aOR) = 0.27, 95% confidence interval (CI) = 0.11, 0.65; CoI: aOR = 0.50, 95% CI = 0.22, 1.13]; the association was only significant for the BI group. Intervention effects were not sustained at 6 and 12 months. There was little evidence that alcohol use acted as a mediator (indirect effect, BI: aOR = 0.84, 95% CI = 0.63, 1.04; indirect effect, CoI: aOR = 0.86, 95% CI = 0.66, 1.03). Conclusions: Among Vietnamese men receiving anti‐retroviral therapy, alcohol reduction counseling interventions appeared to reduce intimate partner violence perpetration immediately post‐intervention, but reductions were not sustained at 6 and 12 months and were not explained by alcohol reduction.